2011
DOI: 10.1016/j.jvs.2010.11.106
|View full text |Cite
|
Sign up to set email alerts
|

The effect of eversion and conventional-patch technique in carotid surgery on postoperative hypertension

Abstract: It is concluded that E-CEA is associated with significantly higher postoperative blood pressure that persists for at least 4 days after surgery. Patients with inadequate preoperative high blood pressure control are particularly at risk after E-CEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 31 publications
(51 reference statements)
2
46
0
2
Order By: Relevance
“…Both techniques have comparable low rates of morbidity and mortality. 5,6 Mehta et al 7 and D emirel et al 8 showed a higher incidence of immediate postoperative HT in patients who underwent carotid endarterectomy by eversion compared with those who were operated by conventional endarterectomy with direct closure or patch closure, with no differences in the incidence of postoperative morbidity and mortality. These were retrospective studies with results covering the first 24 hr postoperatively for the study by Mehta et al 7 and the first 4 postoperative days for the series of D emirel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both techniques have comparable low rates of morbidity and mortality. 5,6 Mehta et al 7 and D emirel et al 8 showed a higher incidence of immediate postoperative HT in patients who underwent carotid endarterectomy by eversion compared with those who were operated by conventional endarterectomy with direct closure or patch closure, with no differences in the incidence of postoperative morbidity and mortality. These were retrospective studies with results covering the first 24 hr postoperatively for the study by Mehta et al 7 and the first 4 postoperative days for the series of D emirel.…”
Section: Introductionmentioning
confidence: 99%
“…These were retrospective studies with results covering the first 24 hr postoperatively for the study by Mehta et al 7 and the first 4 postoperative days for the series of D emirel. 8 In our prospective study, we compared the peroperative and postoperative BP changes for 7 days after the surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Even after unilateral CEA, baroreflex failure syndrome can be a potential complication for hypertensive patients with severe bilateral atherosclerotic lesions. [26] Although there are numerous risk factors associated with the development of postoperative hypertension, it is important to exercise particular caution during the dissection of the CCA in patients with bilateral baroreceptor dysfunction and reduced baroreceptor reserve in order to avoid damaging the vagus nerve and the carotid sinus and also to prevent carotid baroreceptor dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…[2] The results of the current study showed that the baroreflex dysfunction decreased significantly on postoperative day one and remained noticeably lower on postoperative day three; however, on postoperative day three, the baroreflex dysfunction also seemed to show a gradual trend (or increase) towards recovery. [26] The transience of the reduced baroreflex dysfunction might be associated with the recovery of the baroreflex dysfunction through the baroreflex apparatus located on the contralateral side, and the aortic arch a compensatory mechanisms, which may require several days for adaptation. [26] In this study, SAP, MAP and DAP were statistically significantly higher in the contralateral lesion group, compared to the patent contralateral carotid artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation